Gestão da informação e do conhecimento em organizações associadas à sociedade brasileira de gestão do conhecimento - Rodrigo dos Santos Costa (2013)
Based on current conceptions about Knowledge Management practices, this dissertation explored the relationships among such practices in Brazilian organizations. The research was conducted with 94 organizations associated with the Brazilian Society of Knowledge Management. Quantitative data were collected through the application of survey instrument based on Likert scales. Data analysis was conducted in order to establish statistical relationships among practices with organizational learning, communities of practice, enabling contexts (ba), sensemaking, intellectual capital, and strategic information management. The results revealed that the KM practices studied are strongly interrelated.